A Study on US Government Meeting Intelligence: Leveraging Video Analysis for Insightful Decision-Making - Ukani, Parth Mukeshbhai; Makwana, Krisha Pareshbhai; Sompura, Nidhi (Journal of Advanced Research in Service Management, 2023)
This research paper investigates the emerging field of US Government Meeting Intelligence, focusing on the utilization of video analysis for enhancing decision-making processes within government agencies. Government meetings serve as the cornerstone of policy formulation and governance, making the effective extraction of insights from these meetings crucial. Leveraging advanced video analysis technologies, this study aims to revolutionize the way government proceedings are understood, interpreted, and acted upon. The research begins by elucidating the significance of government meetings in shaping public policies, allocating resources, and ensuring accountable governance. It highlights the inherent challenges in managing extensive meeting content and the limitations of traditional manual analysis methods. The study then delves into the core of US Government Meeting Intelligence, exploring the potential of video analysis techniques, including natural language processing, facial recognition, and sentiment analysis, in extracting valuable insights from meeting recordings. Ethical considerations and privacy implications related to the deployment of video analytics in government settings are also addressed. Furthermore, the research offers a practical framework for the implementation of US Government Meeting Intelligence, covering data collection, processing, analysis, and visualization. Real-world case studies and examples illustrate the transformative impact of this innovative approach on government decision-making processes. In conclusion, this study contributes to the evolving domain of government analytics by demonstrating the capacity of video analysis technologies to revolutionize the comprehension and utilization of government meetings. It underscores the potential of US Government Meeting Intelligence to foster transparency, accountability, and data-driven governance, ultimately benefiting government agencies and the citizens they serve.